2022
DOI: 10.3390/diagnostics12020369
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs as Potential Blood-Based Biomarkers for Diagnosis and Therapeutic Monitoring of Active Tuberculosis

Abstract: Early diagnosis increases the treatment success rate for active tuberculosis (ATB) and decreases mortality. MicroRNAs (miRNAs) have been studied as blood-based markers of several infectious diseases. We performed miRNA profiling to identify differentially expressed (DE) miRNAs using whole blood samples from 10 healthy controls (HCs), 15 subjects with latent tuberculosis infection (LTBI), and 12 patients with ATB, and investigated the expression of the top six miRNAs at diagnosis and over the treatment period i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Wagh et al (2017) also reported that miR-16 expression levels in sera of TB patients who received the standard anti-TB drug regimen for six months increased to reach the approximate level of healthy controls (52). Similarly, Kim et al (2022) found that the levels of miR-199b-3p, miR-199a-3p, and miR-16-5p were restored to healthy controls levels after standard anti-tuberculosis therapy (53).…”
Section: Discussionmentioning
confidence: 96%
“…Wagh et al (2017) also reported that miR-16 expression levels in sera of TB patients who received the standard anti-TB drug regimen for six months increased to reach the approximate level of healthy controls (52). Similarly, Kim et al (2022) found that the levels of miR-199b-3p, miR-199a-3p, and miR-16-5p were restored to healthy controls levels after standard anti-tuberculosis therapy (53).…”
Section: Discussionmentioning
confidence: 96%
“…Five downregulated miRNAs (miR-326, miR-346, miR-21-5p, miR-92a-3p, and miR-148b-3p) were identified in serum ( 199 , 220 , 221 ). Studies have shown that the miR-199b-3p, miR-199a-3p, and miR-16-5p levels in whole blood and the miR-424 levels in PBMCs are significantly decreased ( 222 , 223 ). Increased miR-125a-5p levels were observed in TB patients who were treated for 2 months ( 221 ).…”
Section: Mirnas Function As Biomarkersmentioning
confidence: 99%
“…Based on miRNA upregulation and downregulation in LTBI and TB, 39 miRNAs are divided into eight categories. Ten miRNAs (miR-1246, miR-2110, miR-370-3p, miR-28-3p, miR-193b-5p, let-7b-5p, miR-30b-5p, miR-424, miR-365, and 199a-3p) are upregulated only in TB patients ( 223 , 236 238 ). Five miRNAs (miR-374a, miR-26a, miR-142-3p, miR-16-5p, and miR-451a) are downregulated only in TB patients ( 103 , 239 , 240 ).…”
Section: Mirnas Function As Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most promising tools for the diagnosis and therapeutic followup of patients is the use of microRNAs as biomarkers of infectious diseases in blood. 35,36 miRNAs are small, non-coding RNAs, typically 18-24 nucleotides in size, that have an important role in regulating gene expression at the post-transcriptional level and are involved in shaping immunity by regulating gene expression in immune cells. To carry out their regulatory activities, miRNAs bind to their complementary sequence at the 3'untranslated end of the messenger RNA, targeting it for degradation or inhibiting its translation.…”
Section: Traditional Tuberculosis Diagnosis and Micrornas As New Toolsmentioning
confidence: 99%